Improving protection against proximal colon cancer by colonoscopy. (November 2011) - Lasisi, Femi; Rex, Douglas K
Colonoscopy protection against proximal cancer can be achieved, but the level of protection has thus far been less than left colon protection. Improved proximal protection begins with effective right colon bowel preparation, best achieved by split dosing the preparation regimen. Cecal intubation in screening examinations should exceed 95%, and must be documented by photography. Examiners must be proficient in detection of subtle right colon lesions, including serrated lesions as well as flat and depressed adenomas. Effective examination should be demonstrated by meeting recommended targets for adenoma detection.